Editorial - M. Laubscher (Acta Theologica)
Only time will tell whether the current edition speaks knowingly into our “now”. By now, you know that these articles have gone through an extensive blind internal-and-external double peer-reviewed process and eventually got an A or B grading by their peers in the field. Now, after the release of yet another edition, it is perhaps wise to make a few remarks on what lies between the lines as we discern our times. What is this new knowledge we all aspire to be associated with?